2016
DOI: 10.1080/13102818.2015.1136237
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel abiotic stress responsive sulphotransferase gene (OsSOT9) from rice

Abstract: Abiotic stresses may seriously affect plant growth and development. In order to explore new stress tolerance genes in rice (Oryza sativa L.), expression profiles were obtained for leaf and panicle tissues. They were taken at seedling, booting, heading and flowering stages of indica cultivar Pei'ai 64S plants under cold, drought and heat stresses by using the GeneChip Rice Genome Array (Affymetrix), which includes 51,279 transcripts from japonica and indica rice. O. sativa L. cytosolic sulphotransferase-like ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Na+/H+ (AtNHX1) and K+/H+ (AtNHX3) antiporters from Arabidopsis have been demonstrated for improved tolerance (CDS_39398_Unigene_61545) against salt and drought stresses in transgenic poplar [42]. Cytosolic sulfotransferase (OsSOT9) gene from rice has been reported as a novel candidate (CDS_38924_Unigene_60033) concerned to stress tolerance [43]. Wang et al [44] have demonstrated that RPN1a, the Arabidopsis 26S proteasome subunit (CDS_12189_Unigene_22188) is necessary for optimal growth of plant as well as stress responses.…”
Section: Resultsmentioning
confidence: 99%
“…Na+/H+ (AtNHX1) and K+/H+ (AtNHX3) antiporters from Arabidopsis have been demonstrated for improved tolerance (CDS_39398_Unigene_61545) against salt and drought stresses in transgenic poplar [42]. Cytosolic sulfotransferase (OsSOT9) gene from rice has been reported as a novel candidate (CDS_38924_Unigene_60033) concerned to stress tolerance [43]. Wang et al [44] have demonstrated that RPN1a, the Arabidopsis 26S proteasome subunit (CDS_12189_Unigene_22188) is necessary for optimal growth of plant as well as stress responses.…”
Section: Resultsmentioning
confidence: 99%
“…According to the method described in previous studies [31,32], we obtained the experimental materials as follows. Seeds of cultivated Indica rice Pei'ai 64S were sterilized in 0.1% HgCl 2 for 10 min and washed three times under double-distilled water, immersed for 3 days under 25 C with water changed every day; then they were selected and germinated in liquid culture medium at 37 C for 2-3 days.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Therefore, it is necessary to vigorously excavate some genes related to abiotic stress in rice, and use genetic engineering to study and modify them, so that rice has corresponding resistance under different stresses (Filiz and Akbudak 2020). This is of great significance for ensuring the normal growth and development of rice in harsh environments and maintaining stable and considerable yields (Cao et al 2016).…”
Section: Introductionmentioning
confidence: 99%